Exploring the peroxidase activity of ferriprotoporphyrin IX: towards understanding its cytotoxicity in the malaria parasite - Bergh, Wikus (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.